Peningkatan Titer Antibodi Terhadap Avian Influenza Dalam Serum Ayam Petelur yang Divaksin Dengan Vaksin Komersial - Ummu Balqis; Muhammad Hambal; Mulyadi Mulyadi; Samadi Samadi; Darmawi Darmawi (Agricultural Faculty, 2011)
Increasing of antibody titre against avian influenza in serum of vaccinated laying hens with commercial vaccineABSTRACT. The advantages of vaccination are that it reduces the risk of infection, and concurrently reduces morbidity, mortality and shedding of virus. The goal of the present study was to evaluate efficacy of Avian Influenza commercial vaccine based on humoral immunity responses of laying hens. Totally, 20 breakel silver layer hens were used in this research. The laying hens were vaccinated using Avian Influenza commercial vaccine (H5N1). Blood samples were collected from the axilaris vein (left or rigt) one time at prevaccination and repeated three times with an interval of one month at postvaccination. Antibody titres were examined using Hemaglutination Inhibition (HI). The result showed that Avian Influenza commercial vaccine (H5N1) was a good protection because the vaccine was able to trigger protective humoral immunity of laying hens indicated by increasing of antibody titre in serum of vaccinated laying hens during three months.